ANALISIS MARGIN PEMASARAN KOPI BUBUK CAP KELUARGA DI KOTA MANADO - Mukuan, Danny (Sam Ratulangi University, 2017)
Kopi Bubuk Cap Keluarga is one of the famous product in the society, sold in package and also able to catch the society’s attention, this coffee also can compete with other benchmark in Sulawesi Utara. Through Marketing Marginal Analysis, this research expected to increase the taste of the product itself, and also the society’s taste to consume Kopi Cap Bubuk Keluarga, therefore increase the expansion of Kopi Bubuk Cap Keluarga especially in Manado.